Identification of two novel neutralizing nanobodies against swine hepatitis E virus - Chen, Yiyang; Wang, Xueting; Zhang, Meimei; Li, Jinyao; Gao, Xueyan; Nan, Yuchen; Zhao, Qin; Zhou, En-Min; Liu, Baoyuan (Frontiers in Microbiology, 2022)
Hepatitis E virus (HEV) is thought to be a zoonotic pathogen, and causes seriously economic loss in livestock and threatens human public health. However, there has been a lack of efficient antiviral strategies. As a more promising tool to antiviral therapy, nanobodies (also named single-domain antibodies, sdAbs) exhibited higher specificity and affinity than traditional antibodies. In this study, nanobodies anti-genotype 4 HEV ORF2 were screened using phage display technology, and two nanobodies (nb14 and nb53) with high affinity were prokaryotic expressed. They were identified that could block HEV ORF2 VLP sp239 (aa 368-606) absorb HepG2 cells in vitro. And with the animal model built previously, the detection indicators of fecal shedding, viremia, seroconversion, ALT levels and liver lesions showed that the nb14 could completely protect rabbits from swine HEV infection, and nb53 also partially blocked swine HEV infection of rabbits. Collectively, these results revealed that nb14 with perfectly anti-HEV neutralizing activity were expected to be developed as antiviral drugs for HEV.